The national income of Tanganyika, 1952-54 - Peacock, Alan T.; Dosser, Douglas (London: H. M. Stationery Off., 1958)
This report explain the concept of a national income to those unfamiliar with economic statistics.. It also suggest which problems, conceptual and statistical, beset any attempt to apply these principles to a developing country.
Bibliography: p. 73-76.
osa;09/10/17
Loans
Keywords: Income